FAKTOR-FAKTOR YANG MEMPENGARUHI PENURUNAN PRODUKSI MINYAK KELAPA MURNI (LENGIS TANUSAN) DI DESA ANTIGA, KARANGASEM - I Nyoman Sunada (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2021)
The purpose of this study is to identify and describe the factors that influence the decline in the production of virgin coconut oil (lengis tanusan) in Angtiga Village, Karangasem, and the benefits of this research are expected to be information to the world of the catering industry and the public that virgin coconut oil has many benefits. advantages of ordinary vegetable oil. The theory used to solve the problem in this research is